Analysis of consumer behavior and energy calculation for phase end of life on stamped batik products - Much. Djunaidi; Dyah Ayuningtyas (Center for Science and Technology, IAIN Surakarta, 2018)
A product reaches the end-of-life phase when its usage period expires. End-of-life recycling is divided into three categories: reuse, recycle, and landfill. Reuse involves transferring the usage rights to others for the same purpose. Recycling utilizes used goods as raw materials for other products. Landfilling refers to disposing of used clothing at a waste dump site. Consumers have different tendencies regarding expired products, and stamped batik, as a typical product of Solo, undergoes similar treatment at the end of its life cycle. This study aims to analyze consumer behavior toward stamped batik and calculate the energy required in the final product phase. The analysis was conducted using Simapro 3.8.0.0 software. Based on consumer behavior, most stamped batik users repurpose the fabric for cleaning cloths or recycling (48.97%). The energy required for the recycling process of stamped batik is 3.2 kPt. The energy resources needed for landfilling stamped batik amount to 0.085 kPt, while the electrical energy used for landfilling stamped batik is 14.4 MJ per year.